Improved kinetic behaviour of Mg(NH2)2-2LiH doped with nanostructured K-modified-LixTiyOz for hydrogen storage - Gizer, Gökhan (2020)
The system Mg(NH2)2 + 2LiH is considered as an interesting solid-state hydrogen storage material owing to its low thermodynamic stability of ca. 40 kJ/mol H2 and high gravimetric hydrogen capacity of 5.6 wt.%. However, high kinetic barriers lead to slow absorption/desorption rates even at relatively high temperatures (>180 °C). In this work, we investigate the effects of the addition of K-modified LixTiyOz on the absorption/desorption behaviour of the Mg(NH2)2 + 2LiH system. In comparison with the pristine Mg(NH2)2 + 2LiH, the system containing a tiny amount of nanostructured K-modified LixTiyOz shows enhanced absorption/desorption behaviour. The doped material presents a sensibly reduced (∼30 °C) desorption onset temperature, notably shorter hydrogen absorption/desorption times and reversible hydrogen capacity of about 3 wt.% H2 upon cycling. Studies on the absorption/desorption processes and micro/nanostructural characterizations of the Mg(NH2)2 + 2LiH + K-modified LixTiyOz system hint to the fact that the presence of in situ formed nanostructure K2TiO3 is the main responsible for the observed improved kinetic behaviour.